ASSESSMENT OF THE EFFECTIVENESS OF USING INNOVATIVE METHODS IN PERINATAL CARE - Umurzakov, S.M.; Djabbarova, Yu.K.; Urinbaeva , N.A.; Sydikov , A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Objective: to assess the quality of medical services at the Republican Perinatal Center (RPC). Material and methods. Published materials are summarized, which present the results of the implementation of a number of new technologies for the management of pregnant women, women in labor and postpartum women with a high risk of obstetric complications, introduced in the RPC since 2016. A clinical and statistical analysis of the annual reports of the RPC for the period 2017-2024 was carried out. Results. The effectiveness of perinatal care was assessed based on the main indicators of a level 3 center (survival of newborns by weight category, perinatal mortality). Conclusions. The introduction of new technologies for diagnosis, prevention, and treatment of obstetric complications in the perinatal center helps to timely identify the pathology of pregnant women, improve antenatal care for high-risk pregnant women and women in labor, and have reduced perinatal mortality. In the future, a differentiated approach to the implementation of innovative technologies in regional and inter-district perinatal centers will have important practical significance.